Concept of Restorative Justice in the Crime of Money Laundering which is detrimental to the State due to Corruption Crimes - Aniqoh, Ihda; Kurniawan, Bagus Dwi; Pham, Thanh Nga (Lex Journal: Kajian Hukum & Keadilan, 2024)
Every country has the right to resolve money laundering cases through restorative justice in returning assets as an effort to recover state financial losses resulting from criminal acts of corruption through the United Nations Convention Against Corruption (UNCAC) which is signed by 133 countries. The aim of this research is to analyze how the concept of restorative justice is applied in money laundering crimes which are detrimental to the State due to the increasing number of criminal acts of corruption in Indonesia. The type of research used is normative legal research using a statutory approach and a conceptual approach. The results of this research are that the application of the concept of restorative justice in the crime of money laundering which is detrimental to the State due to criminal acts of corruption can be applied in Indonesia as long as it does not conflict with Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Crimes. Corruption Crime. Rules related to the concept of Restorative Justice are contained in the Circular Letter of the Deputy Attorney General for Special Crimes Number: B113/F/Fd.1/05/2010 dated 18 May 2010 and the Letter of the Chief of Police No. Pol. B/3022/XII/2009 concerning the concept of Alternative Dispute Resolution.